2004
DOI: 10.1074/jbc.m403092200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Atypical Protein Kinase C PB1 Domain and Its Mode of Interaction with ZIP/p62 and MEK5

Abstract: Atypical protein kinase C (aPKC) has been implicated in several signaling pathways such as cell polarity, cell survival, and cell differentiation. In contrast to other PKCs, aPKC is unique in having the PB1 (Phox and Bem 1) domain in the N terminus. The aPKC PB1 domain binds with ZIP/p62, Par6, or MEK5 through a PB1-PB1 domain interaction that controls the localization of aPKC. Here, we determined the three-dimensional structure of the PB1 domain of PKC by NMR and found that the PB1 domain adopts a ubiquitin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 52 publications
1
73
0
Order By: Relevance
“…When the p62-PB1AM mutant was mixed with equimolar amount of the PB1 domain from PKCζ (PKCζ-PB1, residues 12-101), the vast majority of these two PB1 proteins co-migrated in earlier fractions, indicating the formation of a stable complex with 1 : 1 stoichiometry ( Figure 2C). By contrast, the p62-PB1BM mutant does not interact with PKCζ-PB1 as reported [35]. We also examined the effect of the p62AM mutation on the interaction between two full-length proteins using the coimmunoprecipitation assay, and the result reaffirms that the p62AM mutant, engineered to destroy the acidic OPCA motif, does not abolish the binding of p62 to PKCζ ( Figure 2A).…”
Section: Both Pb1 Domains Are Indispensable For the Interaction Betwesupporting
confidence: 49%
“…When the p62-PB1AM mutant was mixed with equimolar amount of the PB1 domain from PKCζ (PKCζ-PB1, residues 12-101), the vast majority of these two PB1 proteins co-migrated in earlier fractions, indicating the formation of a stable complex with 1 : 1 stoichiometry ( Figure 2C). By contrast, the p62-PB1BM mutant does not interact with PKCζ-PB1 as reported [35]. We also examined the effect of the p62AM mutation on the interaction between two full-length proteins using the coimmunoprecipitation assay, and the result reaffirms that the p62AM mutant, engineered to destroy the acidic OPCA motif, does not abolish the binding of p62 to PKCζ ( Figure 2A).…”
Section: Both Pb1 Domains Are Indispensable For the Interaction Betwesupporting
confidence: 49%
“…Besides that effector diversity, our report puts forward a novel scaffold role for G␣ q in ERK5 signaling based on its ability to directly interact with both PKC and MEK5. Our data suggest that activation of GPCR would first promote G␣ q /PKC association followed by direct binding or MEK5 to G␣ q , which would in turn favor PKC/MEK5 interaction through their respective PB1 domains (39,40), leading to ERK5 activation (see model in Fig. 6A).…”
Section: Discussionmentioning
confidence: 99%
“…Alignment of the sequences of human PB1 domains reveals a unique cysteine residue in aPKCs, Cys69, located within the conserved OPR, PC and AID (OPCA) motif responsible for binding to par6 and p62 ( Figure 3A). Interestingly, Cys69 is located at the binding interface between PKCι and par6 where it interacts with Arg28, a residue within the basic cluster of par6 involved in PKCι binding (27,79) (Figure 3B). Mutation of Cys69 in PKCι to either isoleucine (C69I) or valine (C69V), the two amino acids most frequently seen at this position in other PB1 domains, has no effect on par6 binding (78).…”
Section: Aurothiomalate (Atm) Inhibits Transformation By Targeting Thmentioning
confidence: 99%
“…aPKCs are thought to be coupled to these signaling molecules via protein-protein interactions involving the PB1 domain of aPKC (25). At least three PB1 domain-containing proteins have been identified that bind to aPKCs via PB1-PB1 domain interactions; p62 (18,79), par6 (21,(80)(81)(82), and Mek5 (79,83). p62 is a scaffold protein that links aPKC to NF-κB downstream of extracellular signals such as tumor necrosis factorα, interleukin-1 and the nerve growth factor (72,84,85).…”
Section: The Phox/bem1 Domain In Oncogenic Pkcι Signalingmentioning
confidence: 99%